Analisis Kreativitas Kegiatan Menggambar Pada Anak Usia 4-5 Tahun Di RA Al-Huda Desa Mekar Sawit, Kecamatan Sawit Seberang, Kabupaten Langkat, Sumatera Utara - Afif Fakhri Hilal MT, Faza Ruyda Hudiya, Nun Zairina, (CV. PUSDIKRA MITRA JAYA, 2022)
Creativity is an important aspect that influences life, one of which is to solve problems effectively. The phenomenon that has existed so far is that the creativity possessed by the community in general is still low. It can be seen that there are still many people who have not been able to produce their own works. This study aims to improve children's drawing creativity from an early age and create a fun teaching and learning atmosphere. This research is a qualitative descriptive research. The type of research used in this research is Classroom Action Research (CAR). Data collection techniques used are observation, interviews, and documentation. The results of this study indicate that there is an increase in children's drawing creativity, children's work is more varied and children have the courage to express and communicate their work. The creativity of drawing gives freedom to develop feelings and skills when children do drawing activities, because drawing is a medium for early childhood to play while learning is more fun and interesting.